Ireland and England: 1798-1922 - Joe Finn (Holder and Stoughton, 1995)
This book provides the reader with a source-based analysis of Anglo-Iris relation from 1798 to 1922. It begins with a coverage of the rebellion of 1798 and looks in detail at the various movements towards home rule and the role of individuals within tem, the course of the Iris potato famine and events up to the establishment of the Iris Free State in 1922